Global Brands and Consumer Ethnocentrism of Youth Soft Drink Consumers in Greater Jakarta, Indonesia - Tasurru, Hammam Haris; Salehudin, Imam (UI Scholars Hub, 2021)
Indonesia is a large market for consumer products targeting youth consumers, with populations of more than 70 million young inhabitants and market size of USD 155 billion. The large size of this potential market attracts foreign products with globallyrecognized brands to enter the Indonesian market. The objective of this study is to explain the purchase intention of youth consumers toward a particular brand of soft drink with global penetration by their perceptions and ethnocentrism. This study obtained response from 156 youths in Greater Jakarta, Indonesia. The resulting data was analyzed using structural equation modeling with LISREL software package. The study found that consumer ethnocentrism decreases purchase intention, both directly and indirectly through brand image. Contrary to the hypothesis, consumer ethnocentrism does not influence corporate image of the global firm, which significantly influences brand image but only slightly impacts purchase intentions directly.